2022
DOI: 10.1007/s41324-022-00488-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of the COVID-19 pandemic in Iran

Abstract: Globally, the COVID-19 pandemic is a top-level public health concern. This paper is an attempt to identify and COVID-19 pandemic in Iran using spatial analysis approaches. This study was based on secondary data of confirmed cases, deaths, recoveries, number of hospitals, hospital beds and population from March 2, 2019 to the end of November 2021 in 31 provinces of Iran from hospitals and the website of the National Institute of Health. In this paper, three geographical models in ArcGIS10.3 were utilized to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The study identify a strong correlation between the COVID-19 variables and the population density [16]. The authors in [17] utilized three geographical models to analyze and evaluate COVID-19 pandemic. Geographic Weight Regression (GWR),Getis-OrdGi*(G-i-star) statistics, and Moran auto-correlation spatial analysis are carried out on data of confirmed cases, deaths, recoveries, and number of hospital beds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study identify a strong correlation between the COVID-19 variables and the population density [16]. The authors in [17] utilized three geographical models to analyze and evaluate COVID-19 pandemic. Geographic Weight Regression (GWR),Getis-OrdGi*(G-i-star) statistics, and Moran auto-correlation spatial analysis are carried out on data of confirmed cases, deaths, recoveries, and number of hospital beds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In certain instances, spatial-based surveys have been undertaken to venture into the field and amass comprehensive data on the pandemic's dynamics. These efforts aim to provide invaluable information that can serve as a lifeline in our battle against infectious diseases, including the formidable adversary that is COVID-19 (Isaza et al, 2023). In this regard, and despite significant advancements in the field of disease management, infectious diseases remain a crucial concern in epidemiology and public health.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution patterns of COVID-19 in Iran have been analyzed in several studies (including Isaza et al, 2023;Nojomi et al, 2021;Sharifi et al, 2022;Raoofi et al, 2020). Rahnama and Bazargan (2020) relied on ArcGIS software and spatial selfcorrelation to analyze the data of individuals diagnosed with COVID-19 between 22 February 2020 and 22 March 2020 (21,638 cases) and found that the provinces of Qom, Mazandaran, Gilan, Qazvin, Isfahan, Semnan, Markazi, and Yazd were situated within the HH cluster.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous studies, Hamadan province was recognized as high-risk areas among its neighboring provinces (i.e., Lorestan, Kurdistan, Kermanshah, Markazi, Zanjan and Qazvin) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%